Risk of malnutrition in a sample of community-dwelling elderly - Martins, Emília (2016)
Portuguese studies evidence situations of malnutrition risk among the elderly, with negative implications for the aging process. It’s important to increase the diagnosis and to identify variables that may mediate the process, in order to sustain socioeducational interventions.